Time-series proteomic study of the response of HK-2 cells to hyperglycemic, hypoxic diabetic-like milieu - Valdés, Alberto (PLoS One, 2020)
During diabetes, renal proximal tubular cells (PTC) are exposed to a combination of high glucose and hypoxic conditions, which plays a relevant role in the development of diabetic kidney disease (DKD). In this work, a time-series proteomic study was performed to analyse the effect of a diabetic-like microenvironment induced changes on HK-2 cells, a human cell line derived from normal proximal tubular epithelial cells. Cells simultaneously exposed to high glucose (25 mM) and hypoxia (1% O(2)) were compared to cells in control conditions for up to 48 h. Diabetic conditions increased the percentage of death cells after 24 and 48 h, but no differences in the protein/cell ratio were found. The relative protein quantification using dimethyl-labeling and UHPLC-MS/MS analysis allowed the identification of 317, 296 and 259 proteins at 5, 24 and 48 h, respectively. The combination of statistical and time expression profile analyses indicated an increased expression of proteins involved in glycolysis, and a decrease of cytoskeletal-related proteins. The exposure of HK-2 cells to high glucose and hypoxia reproduces some of the effects of diabetes on PTC and, with the limitations inherent to in vitro studies, propose new mechanisms and targets to be considered in the management of DKD.